Evaluation of the health care budget impact of secukinumab treatment in patients with ankylosing spondylitis - S. K. Zyryanov; I. N. Dyakov; S. V. Nedogoda; M. Yu. Frolov; A. S. Salasyuk (Современная ревматология)
Objective: clinical and economic analysis of including of secukinumab (SEC) in the essential drug list (EDL) and Federal Reimbursement (ONLS) to ensure the availability of the drug to patients with ankylosing spondylitis (AS) at the expense of health. Material and methods. A budget impact analysis was used. Only cost of drugs was taken into account. Adalimumab (ADA) and infliximab (INF) were used for comparison. Basing on the calculated number of patients treated with these drugs in 2016 from the budget of health care system impact on 3-years budgets of State Guarantee Program (SGP) and ONLS was analyzed. The analysis scenario was based on the replacement of ADA and INF with SEC. Results. Expenditure of a 3-year therapy cycle with SEC amounted to 1.703 million rubles, which was 41.6% less than that with ADA (2.917 million rubles) and 57.7% less than that with INF (4.022 million rubles) in the same period. The budget impact analysis to estimate the cost of SGP demonstrated that the use of SEC during a 3-year period would result in a reduction in expenses by 51.2% (saving of 3.8 billion rubles). When SEC is used within the ONLS, its cost during 3 years will be reduced by 51.9% (savings of 1.9 billion rubles). Conclusion. The inclusion of SEC in EDL and ONLS is appropriately and economically justified, as it enables a substantial reduction in the expenditure of health care budgets to treat patients with AS and to maintain the clinical effectiveness of therapy.